Biogeogens and Human Health - Kumar, Niraj; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2013)
Health of the people is the most important indicator of the development of a nation. Health is a state of complete physical, mental and social well being and not merely the absence of disease or infirmity (as defined by WHO). The state of health of an individual or population depends upon complex interaction of the physical, biological, political and social domains. The environment affects the human health in a big way. People tend to be most susceptible to illness when physically or mentally stressed. Stress, energy and immunity form a closely knit network. Through his experimental findings, the author has brought out this intricate concept of interdependence of biotic (living) and abiotic (non-living) factors in an ecosystem, resulting in an impact on human health, in an explicitly marvelous manner. As a result, a new word (3z(BBiogeogens(3y (Bhas been coined, (3z(Bbio(3y (Bfor living (biotic) , (3z(Bgeo(3y (Bfor non-living (abiotic/geographical/climatic/environment) and (3z(Bgens(3y (Bfor the interactive proceeds of the two. The content included herein is directly concerned with the societal health and gives a clue to many socio-psycho health problems presently not handled with care. It also defines a multidimensional approach for dealing with many psychosomatic and health problems.s
Introducing the Concept of Biogeogens -- Dogma of Biogeogens -- Establishing the concept of Biogeogens -- Our studies on rural/tribal populations -- Supporting Evidences from the Evolutionary History of Man -- Evolution of Alternative System of Medicines is itself an Explanatory Evidence, supporting the theory of Biogeogens.
Keywords: Medicine; Evolution (Biology).; Medicine & Public Health; Medicine/Public Health, general; Evolutionary Biology; Health Promotion and Disease Prevention